دور التسويق السياحي في تعزيز حقوق الزبون السياحي: دراسة استطلاعية لآراء عينة من زبائن بعض الشركات السياحية في مدينة الموصل - عباس، جرجيس عمير; حرحوش، ميادة زيد الخير (جامعة تكريت - كلية الإدارة والاقتصاد, 2021)
أصبحت السياحة في الوقت الراهن تعد من بين الأنشطة الاقتصادية المهمة التي تحرص أغلب دول العالم على تنميتها نظرا للأهمية والدور الكبير الذي تؤديه في اقتصاديات تلك الدول ويهدف البحث الحالي إلى التعرف على عناصر التسويق السياحي بوصفه متغيرا مستقلا بأبعاده المتمثلة بـــ المنتج (الخدمة)، والسعر، والترويج، والمكان (التوزيع) ودوره في تعزيز حقوق الزبون بوصفه متغيرا تابعا في الشركات السياحية في الموصل إذ تواجه هذه المنظمات منافسة قوية ويتحتم عليها المحافظة على زبائنها ونيل ثقتهم، وتم توزيع استمارة الاستبيان على عينة تكونت من زبائن في شركة السياحة في مدينة الموصل وبواقع (50) استمارة وتم استرداد (43) استمارة صالحة للتحليل وتم اختبار عدد من الفرضيات بعلاقات الارتباط والتأثير بين متغيرات البحث باستخدام العديد من الأساليب الإحصائية بالاعتماد على برنامج SPSS، وقد توصل البحث هناك علاقة ارتباط وتأثير في عناصر التسويق السياحي وحقوق الزبون وأن عنصر التوزيع جاء في المرتبة الأولى من بين عناصر التسويق السياحي وعلى ضوء ذلك فقد تم اقتراح بأن تقوم الشركات السياحية بتطوير المتطلبات الأساسية للزبون من خلال توفير وسائل نقل متطورة ومريحة. Tourism has become one of the important economic activities that most countries of the world are keen to develop due to the importance and the great role it plays in the economies of those countries. The current research aims to identify the elements of tourism marketing as an independent variable with its dimensions represented by product (service), price Promotion, place (distribution) and its role in promoting the rights of the customer as a dependent variable in the tourism companies in Mosul, as these organizations face strong competition and it is imperative that they maintain their customers and gain their trust.(50) questionnaires and (45) valid forms were retrieved for analysis, and a number of hypotheses were tested with correlation and influence between the research variables using many statistical methods based on the SPSS program. The first place among the elements of tourism marketing, and in light of this, it has been suggested that tourism companies develop the basic requirements of the customer through providing Advanced and convenient transportation Tourism has become one of the important economic activities that most countries of the world are keen to develop due to the importance and the great role it plays in the economies of those countries. The current research aims to identify the elements of tourism marketing as an independent variable with its dimensions represented by product (service), price Promotion, place (distribution) and its role in promoting the rights of the customer as a dependent variable in the tourism companies in Mosul, as these organizations face strong competition and it is imperative that they maintain their customers and gain their trust.(50) questionnaires and (45) valid forms were retrieved for analysis, and a number of hypotheses were tested with correlation and influence between the research variables using many statistical methods based on the SPSS program. The first place among the elements of tourism marketing, and in light of this, it has been suggested that tourism companies develop the basic requirements of the customer through providing Advanced and convenient transportation
Keywords: السياحة -- مسؤولية حقوق الزبون -- النشاطات التجارية العالمية -- الإدارة التسويقية -- العراق